Struggle of Legal Identity Recognition of Fisherwomen in Ujung Pangkah, Gresik: Feminist Analysis toward Regulation on Fishermen Card and Insurance - Ismail, Naufaludin (Yayasan Jurnal Perempuan, 2017)
This paper will focus on feminist analysis of Law No. 7 of 2016 on the Protection and Empowerment of Fishermen, Fish Cultivators and Salt Farmers and Regulation of the Minister of Marine Affairs and Fisheries No. 16 of 2016 as the legal basis for policy on Fishermen Card and Insurance. This paper will also analyze the experiences of two fisherwomen in Ujung Pangkah, Gresik, East Java who successfully obtained legal identity in the form of fisher card and insurance as a form of legitimacy and recognition of their identity as fisherwomen. The strong patriarchal culture in various society layers, caused the recognition of the political identity of fisherwomen has become difficult, so a feminist analysis toward policy on fisher card and insurance is needed so that women can engage as active subjects in the policy.